Bioremediation of crude oil and heavy metal pollutants in marine environment by biosurfactant, rhamnolipid isolated from Stutzerimonas stutzeri − MW15 - J.B. Sony; W.A. Manjusha; V.S. Sangeetha; Salom Gnana Thanga Vincent; T. Citarasu; J.R. Anusha (Journal of Genetic Engineering and Biotechnology)
Objectives: The current research aimed to study the biodegradation potential of biosurfactants isolated from marine bacteria against crude oil and heavy metals. Methods: Hemolytic activity, oil displacement, drop collapse, tilted glass slide, and emulsification index tests were employed for screening the biosurfactant production efficiency of marine bacteria which was cultured on an enrichment mineral medium. Based on the highest emulsification activity, the most effective bacterial isolates were selected and subjected to biosurfactant isolation. Further, the characterization using TLC, FTIR, and LC-MS were performed. The bacteria and genes that produced biosurfactants have been identified via 16S rRNA sequence analysis. Results: The isolate MW 15 was selected for structural identification given its maximum oil displacement activity, effective surface tension reduction potential, and favourable emulsification index (E24) of 51.3 %. The purified biosurfactant from MW 15 exhibited structural similarities to rhamnolipid biosurfactant. The biosurfactant-produced strain was identified as Stutzerimonas stutzeri by 16Sr RNA sequencing and the nucleotide sequences were deposited in GenBank with accession number PP779775. Mega 11 software was employed for constructing the phylogenetic tree, and it was confirmed that a gene which produces rhamnolipid (rhlA) was present. Conclusion: Totally eight bacteria were isolated from petroleum hydrocarbon-contaminated marine harbour water. The isolate Stutzerimonas stutzeri showed better production of biosurfactants and biodegradation ability when compared with other biosurfactant-produced isolates. The current investigation promises the use of marine bacteria to produce biosurfactants with biodegradability, less toxicity, and eco-friendly nature.